Nuclear magnetic resonance screening of changes in fatty acid and cholesterol content of ovine milk induced by ensiled olive cake inclusion in Chios sheep diets - Symeou, Simoni; Tsiafoulis, Constantinos G.; Gerothanassis, Ioannis P.; Miltiadou, Despoina; Tzamaloukas, Ouranios (My University, 2019)
© 2019 Elsevier B.V. Lipid supplementation of dairy ewe diets has been shown to introduce changes in the fatty acid (FA) profile and cholesterol content of milk. In the present study sheep were fed diets including ensiled olive cake (OC), a conserved by-product of olive oil production, and the lipid content of their milk was assessed in lyophilized samples with nuclear magnetic resonance (NMR) technique. Thirty lactating Chios ewes were allocated into three groups of ten animals fed isonitrogenous and isoenergetic diets which differed in the quantity of ensiled OC inclusion: G0, G500 and G1000 groups with 0, 500, 1000 g (on fresh weight basis) of ensiled OC inclusion per ewe, per day, respectively. Fat percentage, FA profile and cholesterol content were determined in milk samples collected after a 4-week feeding period. Results indicated that saturated FA were reduced by 7.2% and 11.3% in milk samples from the G500 and G1000 groups, respectively. Ensiled OC increased unsaturated FA content by 26.3% and 41.4% and monounsaturated FA content of milk by 30.3% and 45.6% in the G500 and G1000 groups, respectively. Furthermore, the inclusion of 1000 g ensiled OC significantly increased the content of beneficial for human health FA such as conjugated linoleic acids (CLA isomers: 9-cis, 11-trans CLA; 9-trans, 11-cis CLA and 10-trans, 12-cis CLA) by 47.2% and linoleic acid by 14.4% compared to control group. However, any rate of ensiled OC inclusion in the diets of ewes had no effect on milk cholesterol content or milk fat percentage. Overall, the present work provides novel experimental data with NMR fingerprinting of the lyophilized milk lipid fraction, and suggests the use of ensiled OC in sheep rations since it induces desirable changes in ovine milk lipids.
Keywords: Cholesterol; Conjugated linoleic acid; Fatty acids; Olive cake silage; Sheep milk